Farm Fair Voices, Space, History, the Middle Ground and ’the Future’ of Rural Communities - Halsey, John (Australian and International Journal of Rural Education, 2011)
This article is essentially written as two linked parts. The first part considers how space, spatiality and history can contribute to understanding and 'doing something about‘ the sustainability of rural communities. This is done by extensive reference to Soja‘s (1989 & 1996) space and spatial theorising and selective perspectives of history from Williams (1973) and Davison (2005). Essentially I think of space, spatiality and history as a set of conceptual tools for achieving some new traction on the enduring issue of the sustainability of rural communities, and this is the spirit in which the first part of the article is offered. The second part of the article is an overview of the Mapping of Rural Communities project in South Australia and the findings from one data collection site, the Karoonda Farm Fair in the Mallee Region of the state, together with some analysis of findings using space, spatiality, history and White‘s (1999) middle ground concept to generate suggestions about what education may offer in terms of 'The Future‘ of rural communities. I have used 'The Future‘ of rural communities instead of 'sustainability‘ at various times to accentuate the problematic nature of sustainability being a likely outcome, 'going forward‘. As well, 'rural‘ is used as a collective term for locations that are other than capital cities and the remaining population centres in Australia of 100,000 or more. I am aware this is somewhat of a broad-brush approach to defining rural but it is adequate for the purposes of this article; for detailed discussions about defining rural contexts and their characteristics see Walton (1993), Griffith (1996), Mulley (1999), Hugo (2005) and Halsey (2009).